Tingkat Pendidikan Ibu Dan Pola Asuh Demokratif Pada Anak Usia 4 Sampai 6 Tahun Di TK Kuncup Harapan - Era Revika; Irma Erviana; Galuh Tunjung (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Parenting patterns will shape behavior in children. Democratic parenting will make children moreindependent, easy to make decisions, and more confident so that they will get success in the future.Parental education is one of the important things in life because education provides broader insightand influences good parenting for their children.This study aims to determine the correlation between mother's level of education and democraticparenting in children aged 4 to 6 years.This study used a cross-sectional method at the Kuncup Harapan Kindergarten. The subject of thisresearch is the parents of students. The population of this study was all parents of students. 53respondents in this study were selected using simple random sampling. The instrument in this studywas a questionnaire.Results: The results of the analysis (Sig 0.017<0.05) showed a correlation between the level ofmother's education and democratic parenting in students aged 4 to 6 years in Kuncup HarapanKindergarten..Keywords: education level, democratic parenting